Evaluasi Kebijakan Spasial Perlindungan Lahan Pertanian Pangan Berkelanjutan di Kecamatan Kaliwungu Kabupaten Kendal - Widya Kusuma Harniawati; Kismartini Kismartini; Hartuti Purnaweni (PERSPEKTIF, 2021)
This article aims to evaluate the policy of protecting sustainable food agriculture in Kaliwungu District, Kendal Regency. Kaliwungu Subdistrict was chosen as the research location, because the rate of conversion of agricultural land to non-agricultural functions was the highest. The research method used is descriptive qualitative. The data analysis technique used is the results of the GIS (Geographic Information System) analysis to view the land use map from 2011-2017, which will then be analyzed and evaluated the policy of protecting sustainable agricultural land for food, with observational data and documentation. The results showed that there was a change in land use in Kaliwungu District from 2011-2017 amounting to 166.06 Ha. Evaluation of policies for the protection of sustainable food agriculture land in Kaliwungu District, shows that there is a difference in the distribution of the designation of sustainable food agriculture between the Kendal Regency Regional Regulation Number 13 of 2013 and the Kendal Regency Regional Regulation Number 20 of 2011, while the development, research, utilization, guidance, control, transfer of functions, information systems, protection and empowerment of farmers, financing, community participation and supervision in the framework of protecting sustainable agricultural food land have not been implemented. Researchers recommend that the socialization, cooperation between agencies and the implementation of activities to protect sustainable agricultural land should be carried out quickly, carefully and precisely in order to achieve food security in Kaliwungu District in particular and Indonesia in general.